Learning through Digital Devices-Academic Risks and Responsibilities - Emese Beáta Berei; Gabriella Pusztai (MDPI AG, 2022)
The purpose of this study is to examine the risks of learning through digital technology and to design the individual and academic responsibilities. We propose answering the following research questions: Are higher education students and their families equipped with digital devices? What strategy do students use in their individual learning? How frequently do they get involved in various added digital activities (gaming, social media communication, surfing the Internet)? What are the risks of excess time spent online? A total of 2210 higher education students from five European countries, Romania, Slovakia, Hungary, Serbia, and Ukraine, participated in the quantitative study, the data being collected by the Center of Higher Education Research and Development at the University of Debrecen, Hungary in 2019. The analysis of the data is based on the advanced statistical test carried out with the SPSS program. The results indicated that most students come from families that possess essential digital devices (smartphone, PC, notebook) with an internet connection, regardless of the country of origin. The students' learning strategy is mixed: they use the virtual and real environment. More than half of the students declared that they never learn by watching tutorials or listening to audio recordings. Reflecting on themselves, more than a third of them stated that they generally spend too much time online. Daily surfing, gaming, and communicating on social networks are those added activities that significantly multiply their chance of spending too much time in a virtual environment. The binary logistic regression analysis proves that these students have a four times greater chance of developing a concentration crisis. In addition, it is characteristic for there to be a general time management crisis that implicitly contributes to the development of a deadline crisis in learning, and another risk is the duplication of intention to drop out of university.